Educational Narratives of Museum-Based Contextual History Learning for Strengthening Students' Historical Awareness - Yusuf Budi Prasetya Santosa; Ponco Setiyonugroho; Wahyudin Wahyudin (Yayasan Adra Karima Hubbi, 2026)
Background. History education in Indonesia remains heavily reliant on rote memorization, hindering students’ historical consciousness. While museums offer authentic, experiential learning environments, their pedagogical potential remains largely underutilized due to unstructured, passive visits. Purpose. This study aims to analyze the role of museums as contextual history learning media and to develop an integrated three-phase strategy (pre-visit, during-visit, and post-visit) to enhance students’ historical awareness. Method. Employing a literature review methodology, this research synthesizes academic books, peer-reviewed articles, and educational policy documents, analyzed through thematic content analysis. Results. The findings indicate that history learning in schools remains dominated by memorization-oriented and teacher-centered approaches, limiting students’ engagement and historical awareness. In line with previous studies, the use of museums as learning resources can provide more meaningful and experiential learning; however, their implementation is often unstructured and passive. Conclusion. When systematically implemented, this model transforms passive field trips into inquiry-driven learning experiences. It shifts history education from fact-based memorization toward immersive, reflective engagement, ultimately strengthening students’ historical awareness and enabling meaningful connections between past narratives and contemporary realities.